Magnetic Lamp Product Design Development Using QFD Method - Ahmad Wiji Barokah; Eko Wahyu Abryandoko; Faisal Ashari (Journal of Social Science and Economics, 2022)
Lights are always evolving, both in terms of form, features, and function. Magnetic lights are one of the most important objects in the room and are developing. Along with these developments, often the products of magnetic lamps are of less quality. So that the main function of the magnetic lamp is neglected, and it creates weaknesses, both in terms of dimensions and features compared to the previous magnetic lamp design. This gives rise to new ideas for the design of magnetic lighting products that are better in terms of function and added value that can be provided by these products to meet the needs of users or consumers. The success of a product can be measured by how much the existence of the product can be accepted by consumers, and will directly increase profits for the company or producer and vice versa. This study focuses on how to develop and design magnetic lighting product designs according to the wishes of the Customer (students) using the QFD method and identify the attributes of the magnetic lighting products that are prioritized by the Customer (students) using the QFD method with the aim of knowing how to develop and design product designs. Magnetic lamps according to the wishes of the Customer (students) using the QFD method and identifying the attributes of the magnetic lamp products that are prioritized by the Customer (students) using the QFD method. The results of this study are variations in shape a, ideal size, strong material, durable, attractive color, price Rp. 200,000, ease of use, energy saving lamp, attractive shape, color of led lamp can be changed (change color) and identification of process development In the manufacture of magnetic lamps, there are several attributes that are a priority by customers (students) for product development, namely materials that are strong and energy efficient. This development has a fairly high priority, after the two attributes, the development of attractive shapes, and durable materials. Become the biggest development priority. The development of attributes that have a high priority will significantly encourage the fulfillment of customers (students), while developments with low priorities will not have much influence on meeting the needs of customers (students).